Predictive Prenatal Diagnosis for Infantile-onset Inflammatory Bowel Disease Because of Interleukin-10 Signalling Defects. Issue 2 (February 2021) - Ye, Ziqing; Hu, Wenhui; Wu, Bingbing; Zhang, Yueping; Lei, Caixia; Williams, Isabelle; Shouval, Dror S.; Kanegane, Hirokazu; Kim, Kyung Mo; de Ridder, Lissy; Shah, Neil; Ling, Galina; et al.
ABSTRACT: Objectives: Advances in genetic technologies provide opportunities for patient care and ethical challenges. Clinical care of patients with rare Mendelian disorders is often at the forefront of those developments. Whereas in classical polygenic inflammatory bowel disease (IBD), the predictive value of genetic variants is very low, predictive prenatal genetic diagnosis can inform families at high risk of severe genetic disorders. Patients with IL-10 signalling defects because of pathogenic variants in IL10RA, Il10RB, and IL10 develop severe infantile onset inflammatory bowel disease that is completely penetrant and has a high morbidity and substantial mortality despite treatment. Methods: We performed a survey among tertiary specialist paediatric centers of 10 countries on the utilization of predictive prenatal genetic diagnosis in IL-10 signalling defects. We retrospectively report prenatal genetics in a series of 8 families. Results: International variation in legislation, guidelines, expert opinion, as well as cultural and religious background of families and clinicians results in variable utilization of preimplantation and prenatal genetic testing for IL-10 signalling defects. Eleven referrals for prenatal diagnosis for IL-10 signalling defects were identified across 4 countries. We report on 8 families who underwent prenatal preimplantation monogenic testing after in vitro fertilization (n = 2) and/or by amniocentesis/chorion villus sampling (n = 6). A genetic diagnosis was established in 1 foetus and excluded in 7 foetuses (all IL10RA variants). Conclusions: Prenatal genetic testing for IL10R-defects is feasible, yet the legal and ethical considerations are complex and controversial. In some countries, predictive genetics for IL-10-related signalling defects is entering clinical practice.